Transitive Nearest Neighbor Search in Mobile Environments - ZHENG, Baihua (Institutional Knowledge at Singapore Management University, 2007)
Given a query point p, typically the position of a current client, and two datasets S and R, a transitive nearest neighbor (TNN) search returns a pair of objects (s, r) E¸ S x R such that the total distance from p to s and then to r, i.e., dis(p, s) + dis(s, r), is minimum. We propose various algorithms for supporting TNN search as a kind of locationbased services in both on-demand-based and broadcastbased mobile environments. In addition, we develop a novel validation algorithm that allows the clients to verify whether their TNN query answers are still valid after they moved to new positions. Finally, we conduct a comprehensive simulation to evaluate performance of the proposed TNN search algorithms.